Guiding phosphorus stewardship for multiple ecosystem services. Issue 12 (21st December 2016) - MacDonald, Graham K.; Jarvie, Helen P.; Withers, Paul J. A.; Doody, Donnacha G.; Keeler, Bonnie L.; Haygarth, Philip M.; Johnson, Laura T.; McDowell, Richard W.; Miyittah, Michael K.; Powers, Stephen M.; Sharpley, Andrew N.; Shen, Jianbo; et al.
Abstract: The essential role of phosphorus (P) for agriculture and its impact on water quality has received decades of research attention. However, the benefits of sustainable P use and management for society due to its downstream impacts on multiple ecosystem services are rarely acknowledged. We propose a conceptual framework—the "phosphorus‐ecosystem services cascade" (PESC)—to integrate the key ecosystem processes and functions that moderate the relationship between P released to the environment from human actions and ecosystem services at distinct spatial and temporal scales. Indirect pathways in the cascade via soil and aquatic processes link anthropogenic P to biodiversity and multiple services, including recreation, drinking water provision, and fisheries. As anthropogenic P cascades through catchments, it often shifts from a subsidy to a stressor of ecosystem services. Phosphorus stewardship can have emergent ecosystem service co‐benefits due to synergies with other societal or management goals (e.g., recycling of livestock manures and organic wastes could impact soil carbon storage). Applying the PESC framework, we identify key research priorities to align P stewardship with the management of multiple ecosystem services, such as incorporating additional services into agri‐environmental P indices, assessing how widespread recycling of organic P sources could differentially impact agricultural yields and water quality, and accounting for shifting baselines in P stewardship due to climate change. Ultimately, P impacts depend on site‐specific agricultural and biogeophysical contexts, so greater precision in targeting stewardship strategies to specific locations would help to optimize for ecosystem services and to more effectively internalize the downstream costs of farm nutrient management.